ANALISIS PENGIMPLEMENTASIAN AKUNTANSI ASET TETAP BERDASARKAN PSAK NO. 16 DI PT CAHAYA BINTANG MEDAN - Sallim Asrobi Harahap; Budi Gautama Siregar; Aswadi Lubis; Ali Hardana (Jurnal Mahasiswa Akuntansi Samudra, 2023)
Fixed assets are crucial elements in financial statements that require careful monitoring and accurate accounting implementation in accordance with PSAK No. 16 regarding recognition, acquisition, depreciation, disposal, and presentation. This research aims to identify the implementation of fixed accounting and its compliance with PSAK No. 16 at PT. Cahaya Bintang Medan. The study employs a qualitative descriptive method with the subject of research being the financial statements of PT. Cahaya Bintang Medan for the past three years, namely 2019-2021, and data is collected through secondary sources using documentation method. The research findings reveal that the implementation of fixed asset accounting at PT. Cahaya Bintang Medan is in line with PSAK No. 16 until stage of fixed asset depreciation. However, there is a discrepancy in the disposal or termination of fixed assets, as the assets that have been disposed of are not removed from the fixed asset register